Women Empowerment through Cooperatives Savings & Loan Cooperatives - Grace, Fransisca Christine; Radyati, Maria R. Nindita; Utha, Maria (Business and Entrepreneurial Review, 2024)
The role of social capital in women's empowerment through cooperatives has a multiplier effect that contributes significantly to the improvement of the household economy and the economic growth of the community. The object of this research is the Mawar Kusuma Savings and Loan Cooperative (Credit Union) and the Tanjung Sari Women's Cooperative. The total resource persons were 89 people with the technique of determining the sources using purposive techniques. Data was collected using in-depth interviews and questionnaires. This type of research is a mixed method that is qualitative-quantitative. The method of analysis is content analysis. The results of the study indicate that both cooperatives have played a role in developing social and economic empowerment for their members. Contributing to women's empowerment towards sustainable development goals through cooperatives that continue to improve governance that strengthens women's ability to access markets, generate income, and reduce poverty levels. Thus, cooperatives enable many women to be more useful and bring a positive multiplier effect for families and society.